(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2016)
The aim of the present work was to find native plants associated to rice crops for Cd phytoextraction in order to elaborate a strategy for mitigation of contamination by Cd. Field trips were conducted in the study area, located in Daule parish, province of Guayas, western Ecuador. The following species associated to rice crops, those previously recorded in the literature as hyperaccumulators of Cd, were sampled: Azolla sp., Eichhornia crassipes and Limnocharis flava. Tolerance and the bioconcentration factor (BCFs) were tested on plants reproduced in lab. During seven days those were exposed at 0, 0.25, 0.5, 1 and 2 mg/L Cd. Samples were rinsed with distilled water and oven-dried, the biomass was recorded dry on analytic weights. Samples were digested with HNO3 and H2O2, Atomic Absortion Spectrophotometer (Perkin Elmer AAnalyst 100) was used for Cd reading. Species with high tolerance were Eichhornia crassipes and Limnocharis flava; meanwhile Azolla sp. displayed growth inhibition. Tolerance index for Limnocharis is of 116,46 %, and for Eichhornia is of 123,57%. Highest BCFs was recorded for Azolla (6136,13±25,28), followed by Eichhornia (2656,74±1429,10), and finally by Limnocharis (1860±320). Highest concentration of Cd was recorded on the biomass of Azolla (6136±25,28 mg/Kg Cd), roots of Eichhornia (1482±368,41 mg/Kg Cd), and roots of Limnocharis (817,3±100,7 mg/kg Cd). Highest percentages of retrieval on solutions of 46,3% 100% and 30% were found on a treatment of 0.25 mg/L of Cd for Azolla, Eichhornia and Limnocharis, respectively. A mixed culture of Oryza sativa jointly with the herein reported plant species for phytoextraction is recommended to compete with each other for Cd as an strategy for mitigation.